Polymorphism of genes of arterial hypertension among children with obesity and arterial hypertension - G. S. Maskova; A. L. Khokhlov; A. M. Sirotkina (Izdatelstvo OKI, 2021)
Arterial hypertension (АH) among obese children and adolescents is diagnosed with a frequency of 24,8 - 40 % of cases. The pathogenesis high blood pressure (HB) among childhood obesity continues to be studied in connection with the identification of new genetic and epigenetic factors that determine its course. Polymorphism of genes of arterial hypertension can serve as a reason for maintaining increased vascular tone, even if the nutritional status of the child is optimized. The objective was to study polymorphisms of genes of arterial hypertension AGT: 704, AGТ: 521; AGTR2: 1675; еNOS3:786 among children with obesity and arterial hypertension, depending from the dynamics of blood pressure after courses of diet and physical rehabilitation. Materials and methods. The study has included 50 obese and hypertensive children aged 11-14 years who were prescribed diet and courses of special physical exercises for 6 months. We have compared 2 groups of children: children who have had arterial hypertension after treatment («АH6 month +») and children who had no arterial hypertension after treatment («АH6 month -»). The comparison group has consisted of 34 healthy children with normal body mass index and blood pressure. We have performed clinical and instrumental, laboratory examination, anamnestic assessment of heredity, laboratory analysis of genotypic variants AGT: 704, AGТ: 521; AGTR2: 1675; еNOS3:786 among the studied population of children. Results. Comparative analysis of genotypic variants has showed a disproportionate distribution of alleles depending on the dynamics of blood pressure. Among children o «АH 6 month +» there were a predominance of mutant homozygous alleles of the gene AGTR2 AA (A) 45 % (22 %) and a decrease in the frequency a normal homozygous allele GG 9,0 % (9,6 %). We found a greater affinity of the CC homozygote for AGT 704, the CT heterozygote for AGT521 and the CC homozygote for the eNOS gene for the group of children «АH 6 month +» than among children «AH 6 months -» and healthy children. Conclusion. The revealing of causal polymorphisms of genes of arterial hypertension in obese children will allow predicting the risk of developing stable hypertension and determining treatment.